Runaways. 1, Pride & joy - Vaughan, Brian K (Vaughan, Brian K. Runaways, 2009)
When six young friends discover their parents are all secretly super-powered villains, the shocked teens run away from home and straight into the adventure of their lives - vowing to turn the tables on their evil legacy.